KONSTRUKSI REALITAS PEMBUBARAN FRONT PEMBELA ISLAM DAN DEMOKRASI DALAM SURAT KABAR ONLINE - Sovianti, Rina (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This study aims to know the direction of democracy and know the framing of news in Republika.com and Kompas.com, as well as the implications of the dissolution of FPI to development communication. The uniqueness of this research, FPI is a mass organization with a large number of masses but does not have an organizational license. This study uses the paradigm of constructionism, which considers the reality of social life is not a natural reality. Using the Robert N. Entman method to frame news stories coming from Republika.com and Kompas.com. The difference in framing in Kompas.com media and Republika.com is the news source. Republika.com choose a news source from an Islamic background, while Kompas.com choose a news source who is competent in his field is not based on his religion. In the first framing analysis, the level of problem identification and causal interpretation, the two online media have similarities. However, in terms of moral evaluation and treatment recommendation both media have differences. In Republika.com researchers analyzed treatment recommendations is the rejection of FPI activities. FPI has no legal standing. Kompas.com, his treatment recommendation consideration of the dissolution of FPI is to maintain the existence of ideology and basic consensus of the state of Pancasila, the 1945 Constitution, the integrity of the Republic of Indonesia, and Bhinneka Tunggal Ika. Basically, the right to organize is a constitutional right. If there is no fundamental reason, the dissolution of a community organization should not exist. However, FPI is an organization that offers intolerance in the religious field.Â